Reinforced Concrete Beams Subjected to Repeated Drop Weight Impact and Static Load - Syversen, Sebastian; Thrin, Christer (My University, 2022)
When it comes to the structural response of reinforcement concrete beams (RC-beams) subjected to impulse loading, a high energy absorption and large plastic deformation capacity is of interest and not necessarily the load capacity that is of interest like it is for statically loaded structures. The aim of this thesis is to deepen the knowledge of the structural response of RC-beams subjected to single and repeated loading. The RC beams were subjected to single and repeated loading with different drop-weights of 10, 20 and 40 kg from a height of 5 meter. The beams also had different reinforcement diameters of 6, 8 and 10 mm to test how it affects the structural response. The dynamically tested beams were also tested statically to determine the residual capacity. These were then compared to undamaged RC-beams that were statically tested to evaluate any dissimilarities. A literature study was conducted to understand the structural response of the reinforced concrete beams. The study contained load capacity, plastic rotation capacity, internal work, and deflection of the reinforced concrete beams. The experiments on the beams were performed at Chalmers Laboratory, where the response of the RC-beams was captured with a high-speed camera and analysed with Digital Image Correlation (DIC) both statically and dynamically. Afterwards, the plastic rotation capacity and internal work was determined and compared to the predicted response. When the beams were subjected to repeated impulse loading, major damage and localized spalling occurred. The excessive damage and spalling made the capturing of the beams using DIC incredibly difficult and it was difficult to compare to hand calculations. The experimental results showed good correlations to the predicted response. However, there were some deviations in some instances, it is difficult to compare and calculate when the RC-beams were subjected to multiple impacts, although it worked well for a singular impact.
Keywords: Reinforced concrete beams, drop-weight impact, repeated impact loading, 2DOF, internal work, plastic deformation, load capacity, plastic rotation capacity, impact loading, static loading, Digital Image Correlation, DIC